2018
DOI: 10.1002/mc.22843
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping in TERT‐CLPTM1L region identified three independent lung cancer susceptibility signals: A large‐scale multi‐ethnic population study

Abstract: Genome-wide association studies (GWAS) and fine mapping studies have identified multiple lung cancer susceptibility variants in TERT-CLPTM1L region. However, it is still unclear about the relationship between these risk variants and the independent lung cancer risk signals in this region. Therefore, we evaluated the independent susceptibility signals for lung cancer and explored the potential functional variants in this region. Sequential conditional analysis was used to detect the independent susceptibility l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 52 publications
(109 reference statements)
1
6
0
Order By: Relevance
“…Although ERβ plays an important role in CLPTM1L-mediated radioresistance, knockdown of ERβ is not a feasible radiosensitizing method at the moment, because multiple functions of ERβ were still elusive in lung cancer. The present results and those of previous studies suggest that CLPTM1L expression is higher in radioresistant NSCLC cells than in radiosensitive cells, and it is considerably higher than that in normal cells [ 30 , 98 ]. IR upregulated CLPTM1L only in radioresistant cells, whereas it had no effect in most radiosensitive cells.…”
Section: Discussionsupporting
confidence: 78%
“…Although ERβ plays an important role in CLPTM1L-mediated radioresistance, knockdown of ERβ is not a feasible radiosensitizing method at the moment, because multiple functions of ERβ were still elusive in lung cancer. The present results and those of previous studies suggest that CLPTM1L expression is higher in radioresistant NSCLC cells than in radiosensitive cells, and it is considerably higher than that in normal cells [ 30 , 98 ]. IR upregulated CLPTM1L only in radioresistant cells, whereas it had no effect in most radiosensitive cells.…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies also reported that the impact of TERT variation in Asians was stronger than that in Caucasians 45 , 55 . Another study showed that rs2735947 was the most significant SNP in the Caucasians rather than rs2736100 49 . Our findings also confirmed that the C allele and "C" genotype frequencies were indeed higher in Asians than in Caucasians, suggesting that Asians may have longer telomeres that leads to an increased risk of LC.…”
Section: Discussionmentioning
confidence: 99%
“…These evidences imply that the C allele upregulates TERT expression, maintains and prolongs telomere length, and thus increases the risk of LC. In addition, some studies have conducted racial stratification analysis for different types of LC and proved that the influence of TERT variants in Asians is stronger than that in Caucasians 45 , 49 . These results in turn imply that the frequency of TERT rs2736100 variants varies across ethnic populations.…”
Section: Introductionmentioning
confidence: 99%
“…The detailed information about the study subjects in NJMU GWAS was described previously [9]. Genotype imputation for NJMU GWAS was performed using IMPUTE2 and Shapeit v2 with the 1000 Genomes Project (the Phase III integrated variant set release, across 2504 samples) as the reference [14].…”
Section: Study Subjectsmentioning
confidence: 99%